JARGONS USED BY THE MARKETING DEPARTMENT AT HOTEL ARYADUTA MEDAN - Mega Williandani (Jurnal Ilmiah Akomodasi Agung, 2021)
Jargon is a part of language to communicate in the society. A good marketing system certainly shows the good quality of a hotel without overriding the other departments in a hotel.A profession of sales marketing staff department interesting to analyzed. The environment of the job description sometimes created a phenomenon to show off. Jargon is one of interesting to analyzed in the sales & marketing department. This research focuses on understanding how to find out interesting words specifically used in hotels and are more specific in the sales marketing department. The data of the study were taking by the daily conversation between marketing staffs in Aryaduta Hotel Medan. There have six persons in charge as a sales marketing a day. All of sales have specific jargon to communicate, that’s why this research only focuses of the jargon used in the sales &marketing department. The study conducted by qualitative research. The data analyzed based on reality that occur in the present and have occurred in the past based on the article as a reference. The result showedthat an abbreviation exposed to minimize the wrong meaning or errors to understand the real meaning during operational. Acronym showed to make sales person easier pronounced the terminology during operational as an easy way to communicate.